60 GHz wireless data transfer for tracker readout systems: first studies and results - Dittmeier, Sebastian; Berger, Niklaus; Schöning, André; Soltveit, Hans Kristian; Wiedner, Dirk (Journal of Instrumentation, 2014)
To allow highly granular trackers to contribute to first level trigger decisions or event filtering, a fast readout system with very high bandwidth is required. Space, power and material constraints, however, pose severe limitations on the maximum available bandwidth of electrical or optical data transfers. A new approach for the implementation of a fast readout system is the application of a wireless data transfer at a carrier frequency of 60 GHz. The available bandwidth of several GHz allows for data rates of multiple Gbps per link. 60 GHz transceiver chips can be produced with a small form factor and a high integration level. A prototype transceiver currently under development at the University of Heidelberg is briefly described in this paper. To allow easy and fast future testing of the chip's functionality, a bit error rate test has been developed with a commercially available transceiver. Crosstalk might be a big issue for a wireless readout system with many links in a tracking detector. Direct crosstalk can be avoided by using directive antennas, linearly polarized waves and frequency channeling. Reflections from tracking modules can be reduced by applying an absorbing material like graphite foam. Properties of different materials typically used in tracking detectors and graphite foam in the 60 GHz frequency range are presented. For data transmission tests, links using commercially available 60 GHz transmitters and receivers are used. Studies regarding crosstalk and the applicability of graphite foam, Kapton horn antennas and polarized waves are shown.
Gesehen am 08.09.2020